Analisis Isi Buku Teks Pelajaran Bahasa Inggris SMP Ditinjau dari Karakter Kejujuran dan Kedisiplinan - Fidiatun Adiyan (JURNAL PENDIDIKAN DAN SAINS, 2022)
The objective of this study was to identify and understand comprehensively character education in English textbook in terms of honesty and discipline character. The method that used in this research was content analysis method (content analysis). The approach that used was a qualitative approach. The data were collected by reading the textbook intensively and repeatedly then analysis the data of character education. The results of the data analysis found 28-character education values. From these data, the researcher analyses 4-character education in listening skills, then in speaking skills were found 10-character education values, in reading skills there were 13-character education values, and there were 1 character education value of writing skill. The dominant character education values that were analysed was character education in reading skills.